MMP9, Cyclin D1 and β-Catenin are useful markers of p16-positive squamous cell carcinoma in therapeutic EGFR inhibition in vitro - Umbreit, Claudia; Erben, Philipp; Lammert, Anne; Hofheinz, Ralf-Dieter; Aderhold, Marc Christoph; Weiß, Christel; Hörmann, Karl; Schell, Angela; Schultz, Johannes D. (Anticancer research, 2015)
Background/Aim: In the United States 53,640 new cases of head and neck cancer were estimated in 2013. Over 95% of these cases were evaluated as squamous cell carcinoma (SCC). At present, smoking, drinking alcohol, chewing betel and infection with high-risk types of human papilloma virus (HPV) are classified as risk factors of oropharyngeal squamous cancer cell carcinoma (OPSCC). It could be suggested that patients with HPV-positive OPSCC have a better response to chemoradiotherapy than patients without. In many studies, there was observed an inverse correlation between epithelial growth factor receptor (EGFR) expression and HPV status in p16-positive SCC. Therefore, it is of great clinical interest to specify the phenotype of cancer cells in order to further individualize treatment modalities. The aim of the study was to investigate the expression pattern of specific markers in p16-positive SCC cells after stimulation with lapatinib and gefitinib. Materials and Methods: We incubated p16-positive CERV196 cells with lapatinib and gefitinib (2 μg/ml) and after 5, 24 and 96 h determined E-cadherin, vimentin, matrix metalloproteinase-9 (MMP9), cyclin D1 and β-catenin by immunocytochemistry, enzyme-linked immunosorbent assay and quantitative polymerase chain reaction (PCR). Results: We found an increase of E-cadherin and a decrease of vimentin in unstimulated cells. We detected an alteration of expression of vimentin and E-cadherin level after treatment with lapatinib and gefitinib. We demonstrated a statistically significant lapatinib- and gefitinib-induced repression of cyclin D1, MMP9 and β-catenin in CERV196 cells dependent on incubation time. Conclusion: Cyclin D1 and MMP9 expression profiles may represent an early measure of sensitivity and level of response to lapatinib and gefitinib. The presented cell culture model is, therefore, well-suited for further study of epigenetic regulation of molecular targeted-therapy by EGFR inhibition and prevention of mesenchymal transition in p16-positive SCC cells.
Gesehen am 22.02.2018